By Rail and Mail: Understanding the Significance of Colonial Architecture for Mass Transport and Communication in The Philippines - Paredes-Santillan, Caryn; Manalo, Michael F.; Pinlac, John Clemence M. (MAJ - Malaysia Architectural Journal, 2025)
All over the world, mass transport and mass communication systems are the backbone of societal development. In the Philippines, during the turn of the century, the archipelagic landscape was challenging for the colonial government to manage. Thus, establishing efficient systems for transporting goods and people was fundamental to nation-building. Manila’s first post office was established in 1783, becoming Branch No. 31 of the Spanish Postal System. During the American colonial period, city planner Daniel Burnham earmarked a choice spot near the banks of the Pasig River as the site of the Manila Central Post Office Building. On the other hand, the Ferrocarril de Manila a Dagupan was inaugurated by the Spanish colonial government in 1892. The American colonial government further expanded the railway lines. Thus, colonial transport and communications served as the fountainhead of the growth of the national economy and supported commercial agriculture and other industries. This paper seeks to understand the significance of colonial architecture in the Philippines, built specifically for mass transport and communication. This will undertake a formal and spatial study of select structures and propose rubrics to determine their significance. Ultimately, a holistic understanding of their significance is hoped to aid conservation.